(untitled) (World Bulletin of Public Health, 2025)
Kawasaki disease (KD) and multisystem inflammatory syndrome in children (MIS-C) share overlapping inflammatory features, yet they differ substantially in epidemiology, cardiac involvement, and clinical severity. This review compares their cardiovascular and clinical characteristics to clarify key distinctions. KD predominantly affects children under five years of age and shows coronary artery abnormalities in fewer cases. By contrast, MIS-C occurs in older children and adolescents, is more common in Black and Hispanic populations, and demonstrates more severe cardiac involvement, with exhibiting coronary dilation and majority presenting with shock or depressed ventricular function. Cardiac MRI in MIS-C frequently reveals diffuse myocardial edema without fibrosis, and left ventricular strain is significantly reduced compared with KD. MIS-C also presents with broader multisystem involvement, including gastrointestinal, neurological, and MASlike inflammatory features. These differences highlight that, despite superficial overlap, KD and MIS-C represent distinct clinical entities requiring tailored diagnostic and therapeutic approaches.